Exploring barriers and facilitators of primary care physicians towards optimising statin therapy in patients with hyperlipidaemia in the very high-risk group: a qualitative study in Singapore - Chun Yen Beh; Rose Wai-Yee Fok; Lay Hoon Goh (BMJ Open)
Objectives To explore the perspectives of primary care physicians with regard to the barriers and facilitators towards optimising statin therapy in patients with hyperlipidaemia in the very high-risk group.Design Qualitative descriptive study.Setting Four polyclinics in a public primary care institution in Singapore.Participants Seven men and five women working as primary care physicians were recruited for in-depth interviews.Results The major barriers to statin optimisation identified were patients’ lack of knowledge and awareness, patients’ fear of side effects, negative external influences on patients, poor doctor–patient relationship, time constraint during consultations, physicians’ unfamiliarity with guidelines, low health literacy among the local population and lack of strong national policy. The major facilitators identified were patient education, providing continuity of care, improving electronic medical record systems’ capabilities, physician education and public education.Conclusion We identified several important barriers and facilitators of statin therapy optimisation in this study. This information offers insights into the development of a multipronged approach to address barriers across different levels with the aim of optimising statin use, reducing cardiovascular events and improving patient outcomes.